The Role of Local Communities in the Development of Baha Tourism Village in Badung Regency - Pertiwi, Luh Ayu Cahya; Negarayana, Ida Bagus Putra; Subrata, I Made (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research is a type of qualitative research using interview, observation, documentation, and literature study methods. The informants of this research are 14 informants who are indigenous people of Baha village and have an understanding & experience related to the topic of this research. The purpose of this study is to determine the form of role played by the local community in Baha Tourism Village. This study reveals the involvement of 5 forms of local community roles in Baha village in the development of tourism villages, namely: (1) Form of role as initiator, (2) Form of role as implementer, (3) Form of role as participant, (4) Form of role as reviewer/monitor, and (5) Form of role as beneficiary. In its development, the Community in Baha Tourism Village is involved in all five forms of roles, although there are still obstacles, especially in funding and HR training. Overall, this conclusion shows that active and diverse involvement from the community plays a major role in creating sustainable tourism development in Baha Tourism Village.